Surviving a Dark Age: The Oldest Baleen-Bearing Whales (Cetacea: Chaeomysticeti) of Pacific South America (Lower Miocene, Peru) - Francesco Nobile; Olivier Lambert; Giovanni Bianucci; Eli Amson; Mark Bosselaers; Giulia Bosio; Luca Pellegrino; Elisa Malinverno; Claudio Di Celma; Mario Urbina; Alberto Collareta (Life, 2025)
The evolution of baleen whales (Mysticeti) comprises two main phases, namely, (i) a Paleogene phase, which saw the diversification of stem lineages, and (ii) a Neogene phase, dominated by modern-looking, toothless, baleen-bearing forms in the monophyletic group Chaeomysticeti. These two phases are separated by a global turnover event coinciding with a gap—or “dark age”—in the mysticete fossil record. This dark age occurred between 23 and ~18 Ma and is apparently detected worldwide, except in Zealandia. Here, we report on a new mysticete fossil from the Lower Miocene (Burdigalian: ~19.2 Ma) strata of the Chilcatay Formation cropping out at the newly discovered locality of Cerro Tiza (East Pisco Basin, Peru), which represents a limited but precious testament from the last phase of the baleen whale dark age. Two previously mentioned, slightly geologically younger fossils from the same formation are also reappraised herein, revealing the occurrence of at least another baleen whale taxon in the upper Chilcatay strata—one that belongs in the mysticete crown group. Although the Early Miocene remains a problematic time interval for the fossil record of baleen whales, our new results encourage the search for mysticete fossils in the Lower Miocene strata of the East Pisco Basin, whose basin fill preserves a cornucopia of extraordinarily informative marine vertebrate fossils of the Cenozoic age, as well as in coeval deposits worldwide.